Abortion & 'artificial wombs': would 'artificial womb' technology legally empower non-gestating genetic progenitors to participate in decisions about how to terminate pregnancy in England and Wales?. Issue 1 (21st May 2021) - Romanis, Elizabeth Chloe
Abstract: 'Artificial womb' technology is highly anticipated for the benefits it might have as an alternative to neonatal intensive care and for pregnant people. In the bioethical literature, it has been suggested that such technology will force us to rethink the ethics of abortion. Some scholars have suggested that a pregnant person may be entitled to end a pregnancy but, with the advent of ectogestation, they may not be unilaterally entitled to opt for an abortion where the other genetic progenitor does not agree. Following two high-profile cases in England and Wales in the late 70s and 80s, English law is clear that genetic progenitors who do not gestate have no say in abortion decisions. It might be argued, however, that ectogestation casts doubt on the exclusion of all claims by genetic progenitors. In this article, I assess what a legal challenge to a decision to opt for abortion might look like with the advent of this technology, by examining whether genetic progenitors have the locus standi or grounds to seek an injunction to prevent abortion. I argue that such a challenge is unlikely to be successful.